Consumer Satisfaction towards Coca Cola and Pepsi – A study on Specific Region of Punjab - Kaur , Rajwinder; Kaur, Gagandeep (Gyan Management Journal, 2019)
Customer satisfaction is very important for the Company who is producing any kind of product for the people. Because now a day’s customers who are purchasing the products they have huge knowledge of various other similar products. This study basically focuses on consumer satisfaction towards Coca Cola and Pepsi. Various objectives were set for this study and for interpretation SPSS and Excel are used. This paper explores the satisfaction of customers regarding these two beverages and results and findings are drawn.